Seismic Characterization of Tertiary-Cretaceous Formations of Lake Sub-Basin, Borno, Nigeria - Omolaiye, G. E. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2026)
The Borno Basin is a frontier basin within the Mesozoic–Tertiary African rift system that originated in the Early Cretaceous and is situated in northeastern Nigeria, part of the Mega-Chad Basin. This study integrates 3D seismic interpretation with limited well control to delineate the subsurface structural framework of Block 1 within the Lake Sub-Basin. Interpreted seismic horizons range from 250 ms to 3000 ms, indicating progressive eastward thinning of sedimentary units that reflect regional tectonostratigraphic variations. Structural analysis identifies simple anticlines within the Cretaceous succession as the dominant trapping structures, whereas fault systems exhibit significant deformation and poor lateral continuity. Most faults terminate at the angular unconformity separating Cretaceous and Tertiary strata, highlighting a major tectonic discontinuity. Two principal fault types were recognized: deep-seated synthetic faults propagating upward from the basement and antithetic relief faults confined to the sedimentary section. Fault orientation statistics show NW-SE trends as the most prevalent (45%), followed by NS (21%), NE–SW (27%) and E-W (7%) orientations, thereby refining earlier interpretations that emphasized NE-SW dominance. The results suggest that the Borno Basin is characterized by gentle folding, multidirectional faulting, and variable sediment thickness. These structural insights enhance understanding of the basin’s tectonostratigraphic evolution and improve constraints on hydrocarbon prospectivity in this underexplored frontier region.